PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP PENINGKATAN AKTIVITAS DAN HASIL BELAJAR FISIKA SISWA KELAS X MIA 1 MAN 1 BANJARMASIN PADA KONSEP OPTIK GEOMETRI - Hasanuddin, Hasanuddin (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2018)
The aims of study are to determine the effect of Problem Based Learning model in an effort to improve students' physics learning outcomes on the subject of Pressure. The method used in this research is Classroom Action Research (Classroom Action Research). This study was conducted in MAN 1 Banjarmasin academic year 2016/2017. The subjects of the study were students of class X MIA 1 MAN 1 Banjarmasin as many as 26 students. The instrument used in this research is an objective test of multiple choice type with four options (option) used to find out the improvement of students' physics learning outcomes, observation sheet to know the process of learning in the classroom, and questionnaire to know the student response to the model of Problem Based Learning. From the results of this study can be concluded that the application of learning models based on problems can improve student physics learning outcomes class X MIA 1 MAN 1 Banjarmasin.